2010
DOI: 10.1111/j.1471-0528.2009.02467.x
|View full text |Cite
|
Sign up to set email alerts
|

A 1‐year follow up of psychological wellbeing after subtotal and total hysterectomy—a randomised study

Abstract: Objective To compare subtotal abdominal hysterectomy (SH) and total abdominal hysterectomy (TH) regarding influence on postoperative psychological wellbeing and surgical outcome measurements.Design A prospective, open, randomised multicentre trial.Setting Seven hospitals and one private clinic in the south-east of Sweden.Population Two-hundred women scheduled for abdominal hysterectomy for benign conditions were enrolled in the study; 179 women completed the study (94 SH and 85 TH).Methods Four different psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
2
26
0
3
Order By: Relevance
“…15,21 The randomised study was conducted between 1998 and 2004, and the follow-up study was performed between May 2011 and April 2012.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,21 The randomised study was conducted between 1998 and 2004, and the follow-up study was performed between May 2011 and April 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, we used two validated generic QoL forms (the Psychological General Well-Being and Women's Health Questionnaire) in the primary study, and found no significant difference between the modes of hysterectomy on any occasion of assessment, up to 1 year after surgery. 21 It therefore seems conceivable that even a pelvic floor-specific Table 3. POP-Q measurements and occurrence of pelvic organ prolapse preoperatively, and at a median of 11 years after abdominal subtotal and total hysterectomy…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few variables were not normally distributed and consequently we used nonparametric statistical tests for comparison of groups whenever possible. To maintain consistency with our previously published articles 6,7 we chose to use mean and SD in this article. The use of median in the headings of Tables 3 and 4 may be seen as inappropriate from a strictly academic point of view.…”
Section: Sirmentioning
confidence: 99%
“…(Persson et al, 2010b) In addition, they also measured the serum concentration of sex hormones in the patients. The authors failed to find any significant differences between the two groups in any of the psychometric tests.…”
Section: Total Versus Subtotal Hysterectomymentioning
confidence: 99%